Optimization of Single layer Antireflection Coating for Infra-Red Spectrum on Silicon Substrate for Solar Cell Applications - Kumar, Sunil (International Journal of Computer Sciences and Engineering, 2025)
Antireflection (AR) coatings are widely applied on optical devices for not only reducing the undesired reflection loss from the surfaces of the devices, but also for improving the contrast of the image of optical systems. Without the application of AR coatings on optical devices, the partial reflected light from the surfaces results in the formation of ghost images on the image plane, which reduces the contrast of the optical image. In general, the construction parameters of the optimal AR coating design for substrates with different refractive indices are different, thus the substrates should be coated in separate deposition runs. For saving time and reducing cost, this is of practical importance for a commercial thin-film coating shop if different substrates need to be AR-coated. The present work has been carried out to investigate the optimum values of reflectance as a function of wavelength in the infra- red region. The reflectance has been reduced from 32% of silicon surface to less than 1% using ARC film.